Biology of the Afrotropical Sepedonella nana (Diptera: Sciomyzidae), whose larvae feed only on freshwater Aulophorus furcatus (Oligochaeta: Naididae) - Vala, Jeanclaude; Gbedjissi, Louis Ghélus (Zootaxa, 2011)
All studies during the last six decades have stated that sciomyzid larvae are strictly malacophagous. However, the Afrotropical sciomyzid Sepedonella nana species was found in this study to feed only on the small freshwater oligochaete, Aulophorus furcatus. The divergent oligophagous feeding behaviour of this species was investigated. The physical attributes of the egg, first-, secondand third-instar larvae, and the puparium are described. Four types of sensilla—coeloconicum, trichodeum, chaeticum, and styloconicum—are present with a characteristic distribution on each tagma. Each thoracic segment is distinguished by presence of a pair of Keilin’s organ on ventral surface. Each abdominal segment has eleven pairs of the same sensilla types; their variable locations are presented. Population dynamics of the adults are shown from our field investigations in permanent and temporary freshwater biotopes during 1996–2008. The life cycle of the species is presented from our field observations and laboratory experiments. Among the 62 species of Afrotropical Sciomyzidae, this is the eighth species for which life-cycle is entirely resolved.